A population analysis of self‐management and health‐related quality of life for chronic musculoskeletal conditions. (2nd November 2015) - Hoon, Elizabeth A.; Gill, Tiffany K.; Pham, Clarabelle; Gray, Jodi; Beilby, Justin
Abstract: Background: There is growing policy emphasis on self‐management as an essential component of musculoskeletal chronic care models. Underpinning this drive is the assumption that with correct 'informational' framing people will better manage their condition's progression and thereby maintain quality of life. Objective: To assess associations between self‐management behaviours and health‐related quality of life for people with chronic musculoskeletal conditions. Design: Using survey data from health census and follow‐up structured telephone interviews, linear regression (cumulatively adjusted for potential confounders) and logistic regression examined associations between use of specific self‐management behaviours and quality of life. Setting and participants: A total of 885 respondents (2012) who indicated still having a musculoskeletal condition reported in a 2010 health census (Port Lincoln, South Australia). Variables: Specific self‐management activities, age, sex, education, marital status, smoking, comorbidities and pain. Outcome measure: EQ‐5D‐5L. Results: Exercise (63%) and diet (19%) were the most commonly reported self‐management activities used to manage musculoskeletal conditions. About 24% reported not using any specific self‐management activities. Involvement in self‐management showed no association with quality of life, with and without adjustment for confounders. Diet had a negative association with quality of life as did use of formal support (self‐management course or community group support). Discussion: Taking a real‐world perspective, these findings raise important questions about how people currently engage with self‐management activities and the kinds of outcomes that can be expected from undertaking these activities. The timing of people's uptake of self‐management within the musculoskeletal disease continuum is an issue requiring further attention in both research and practice.